EVIDENCE INFORMED POLICY PADA PROGRAM TIKET ONLINE TAMAN SATWA KEBUN BINATANG SURABAYA - Inka Mustika Sari; Arimurti Kriswibowo (Journal Publicuho, 2021)
Surabaya Zoo Animal Park is one of the tourist attractions in the city of Surabaya with increasing visitors every year. Currently, during the pandemic, the Surabaya Zoo's Animal Park has used a new innovation, namely a policy in the form of an online tourist admission ticket program. This has resulted in a decrease in the number of visitors at the Surabaya Zoo's Animal Park. This study aims to determine how evidende informed policy is in the online ticketing program at the Surabaya Zoo's Animal Park. The type of research used in this article is to use a qualitative approach. The results showed that the process of evidence informed policy has been implemented but there are still many people or visitors who do not understand this program. The conclusion of this research is that the process of evidence informed policy that occurs is not yet optimal, this can be seen from the indicators of evidence informed policy.